Resident’s Perceptions on Impacts of Hosting the Guimaraes 2012 European Capital of Culture: Comparisons of the Pre- and Post Periods - Remoaldo, Paula (2016)
Residents tend to have high expectations regarding the benefits of hosting a mega- event, in particular the creation of new infrastructure, growth in GDP and employ- ment, image enhancement and the spin-offs of attracting tourists and fostering sustainable growth of the cultural supply (Jeong and Faulkner 1996; Deccio and Baloglu 2002; Gursoy and Kendall 2006; Getz 2008; Langen and Garcia 2009; Ritchie et al. 2009; Gursoy et al. 2011; Palonen 2011). Nevertheless, they normally recognise that some costs will be incurred (Kim and Petrick 2005; Kim et al. 2006; Ritchie et al. 2009; Gursoy et al. 2011; Lee et al. 2013). So, it was not surprising that the nomination of Guimaraes, a small city in the northwest of Portugal, as one of the two European Capitals of Culture in 2012 (2012 ECOC), had raised great expectations in the local community vis- a-vis its socio-economic and cultural benefits. Our research was designed to examine the Guimar~aes residents’ perceptions of the impacts of hosting the 2012 ECOC, approached at two different times: before and after the event, to try and capture the evolution of the residents’ assessment of its impacts. From the empirical literature, we know that residents’ perceived impacts tend to change as time goes by (Kim et al. 2006; Ritchie et al. 2009; Gursoy et al. 2011; Lee et al. 2013). The data were gathered via two surveys applied to Guimaraes residents, one in 2011, before the event, and the other afterwards, in 2013. The Guimaraes residents’ assessment was thought to be essential to get an accurate appraisal of the impact of the mega-event as they were a main part of the hosting process. 2012 ECOC impacts were mainly felt by local people who, in most cases, will go on feeling them in the short and long term. The research was thought to be socially pertinent as the opinions collected through the surveys can help to prevent repeating mistakes when similar mega- events are organised in the future, and to increase the positive impacts derived from hosting them. When we talk about the social pertinence of the empirical results, we want to stress that the expertise acquired can be useful to any host city or country.